Equivalent matching model of a regulated two-stage turbocharging system for the plateau adaptability. (October 2016) - Li, Hualei; Zhang, Guozheng; Zhang, Huiyan; Shi, Lei; Yang, Mingyang; Deng, Kangyao
The matching problem becomes much more difficult between a regulated two-stage turbocharging system and a diesel engine when they are required to work at different altitudes. This is mainly because there are three or even four main variables to be determined for a regulated two-stage turbocharging system, and the change in the operating altitude also extends the matching problem from a two-dimensional problem of the speed and the load to a three-dimensional problem of the speed, the load and the operating altitude. An optimal scheme for a regulated two-stage turbocharging system should be determined to optimize the plateau adaptability based on the relationship between the matching point, the desirable pressure ratio distribution and the operating altitude. Therefore, a theoretical study on matching a regulated two-stage turbocharging system to a diesel engine at different altitudes is conducted in this paper. The turbine equivalent area of a regulated two-stage turbocharging system is derived on the basis of the turbine flow characteristic model with the thermodynamics equations and the mass and energy conservation of the turbocharging system. The speed and altitude ranges are discussed with the results calculated by the proposed matching model in MATLAB software. Then the simulations with GT-Power software are carried out to validate the application of the equivalent matching model. The calculated results show that the problem of the speed range of the regulated two-stage turbocharging system at different altitudes can be converted to the speed range of a matching scheme based on different pressure ratio distributions at a constant altitude. The altitude range of the regulated two-stage turbocharging system is mainly affected by the matching speed and the bypass flow rate ratio. The validation results of the GT-Power model show that the plateau adaptability of the matched regulated two-stage turbocharging system can be investigated effectively using the equivalent matching model. Therefore, the equivalent matching model can be utilized to achieve a reasonable selection of the matching speed and it can simplify the matching problem of the regulated two-stage turbocharging system at different altitudes.